(untitled) (Islas, 2023)
Introduction: The objective of this article is the presentation, description and archival history of the manuscript of the Cuban buffo theater Amor y Lealtad collected within the Coronado collection of the Universidad Central «Marta Abreu» de Las Villas. Methods: The article begins with a necessary introduction on the history of Coronado’s bibliographic collection and a study of the manuscript using the tools and methods of Paleography is carried out. Results: Among the results are the external description of the manuscript. Its datation, the verification of its authorship. The research also stablishes the trades of the manuscript as a representative of the Cuban buffo theater. Conclusions: The manuscript is dated 1892, it is a copy written as a libretto to be sent to the Censorship. Its characteristics allow it to be classified as a dramatic text belonging to the Cuban buffo theater of the 19th century, specifically to the second stage of the genre.